Evaluation of the Toxocell Latex Agglutination Test as Screening Test and Distribution of Toxoplasma Antibodies among Sexually Active People in Najaf City - Hayder M. Samaka; Abdullah O. Alhatami; Kareem G. Mohammed (Kufa Journal for Nursing Sciences)
Objectives: The present study was intended to reveal the validity of Toxocell (Biokit, Spain) latex agglutination test as screening test. The rate of toxoplasma antibodies distribution in randomly selected subjects was estimated. The sensitivity and specificity of the test were conducted in comparison to the "gold standard" reference test Enzyme-linked Immunosorbent Assay (ELISA, BioCheck, Inc).